2017
DOI: 10.1007/s10714-017-2225-8
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic perfect fluids in local thermal equilibrium

Abstract: Every evolution of a fluid is uniquely described by an energy tensor. But the converse is not true: an energy tensor may describe the evolution of different fluids. The problem of determining them is called here the inverse problem. This problem may admit unphysical or non-deterministic solutions. This paper is devoted to solve the inverse problem for perfect energy tensors in the class of perfect fluids evolving in local thermal equilibrium (l.t.e.). The starting point is a previous result (Coll and Ferrando … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
108
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 16 publications
(109 citation statements)
references
References 14 publications
1
108
0
Order By: Relevance
“…We have already shown [1] (see also the recent paper [2]) that the notion of l.t.e admits a purely hydrodynamic formulation: a perfect energy tensor T evolves in l.t.e if, and only if, the hydrodynamic quantities {u, ρ, p} fulfill the hydrodynamic sonic condition (ρdṗ −ṗdρ) ∧ dρ ∧ dp = 0 .…”
Section: Classical Ideal Gas: Hydrodynamic Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…We have already shown [1] (see also the recent paper [2]) that the notion of l.t.e admits a purely hydrodynamic formulation: a perfect energy tensor T evolves in l.t.e if, and only if, the hydrodynamic quantities {u, ρ, p} fulfill the hydrodynamic sonic condition (ρdṗ −ṗdρ) ∧ dρ ∧ dp = 0 .…”
Section: Classical Ideal Gas: Hydrodynamic Approachmentioning
confidence: 99%
“…Elsewhere [1] [2] we have shown that the system (1) admits a conditional system for the hydrodynamic quantities {u, ρ, p}:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…the determination of the set T F of all perfect energy tensors corresponding to all possible evolutions of the set F of all perfect fluids. In [6] we have also solved the generic inverse problem for a perfect energy tensor T , i. e. the determination of the set F T of all perfect fluids for which T is the energetic description of a particular evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, because of its practical applications, solving a specific direct problem for a family of fluids may be more interesting than to solve the generic one. We have studied in [6] the specific direct problem for the family of the generic ideal gases, i.e. those defined by the equation of state p = knΘ.…”
Section: Introductionmentioning
confidence: 99%